EVALUASI PERUBAHAN STRUKTUR AKIBAT SUBSTITUSI PARSIAL ION Mn +2 DAN ION Ti PADA M HEKSAFERIT BaFe 12-2X Mn MENGGUNAKAN ANALISIS RIETVELD - Widiyanto, Widiyanto; Priyono, Priyono; Nurhasanah, Iis (BERKALA FISIKA, 2011)
Cationic interaction of Mn+2and Ti +4substitution on conventional hexaferriteBaFe O have been studied using X-ray diffraction (XRD) and analysis by the Rietveld method. These Research was conducted by combining compound of Fe O12 19 TiO2 to form (Fe,MnTi)2O phase3BaCO3 phase and heated at 1200. Then, Compound of (Fe,MnTi)0 C to form of BaFe12-2xresult of rietveld analysisshowed that the composition of Hexaferrite BaFe22 3, MnCO and3O phase mixed withMn Ti O3x x 19 compounds. The as main phase and Fe2Oas a second phase. At all compositions showed that the largerfraction of ions Mn+23 and Ti+4 ions able to change latice parameter from the volume unitcell of conventional hexaferrite. The results reatveld iteration of the phaseBaFe MnTiO (x = 1.0) obtained values of lattice parameters a = 5.9116 Ǻ and c =23.2532 Ǻ or shrinkage abaut 5,0 % volume unit cell and at BaFe Mn Ti O10 19 (x=2.5)the volume unit cell 7,0% lower than conventional hexaferrite.Keywords: Rietveld, unit cell, substitusi io, hexaferrite, 12-2x7 2.5 2.5 19Mn Ti Ox x 19